Education in Indonesia - Suryadarma, Daniel; Jones, Gavin W. (Indonesia update series, 2013)
Examines the major developments in education in Indonesia. Drawing on the expertise of some of the most knowledgeable people in the field, it identifies the challenges facing the sector and offers recommendations on how these challenges could be overcome.